REGULATION OF SEISMIC LOAD ON BUILDINGS SEISMIC DEVICES - Kh. N. Mazhiev; D. K-S. Bataev; Kh-M. S. Dukhaev; K. Kh. Mazhiev; A. Kh. Mazhieva (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The issues of regulation of seismic loads on structures using kinematic supports of highstrength concrete on the impregnated coarse aggregate and seismic isolation bearings Belleville. The results of experimental studies related to the obtaining of a new coarse aggregate and construction of seismic isolation bearings. Addresses the issues of interaction forces in thehemispherical supports vibration process.